PENGARUH AMBANG -BERTALUD PADA BAK KONTROL DI SALURAN TERBUKA TERHADAP KONDISI ALIRAN - Agus Suhardono; Joko Setiono; Mona Shinta (Prokons: Jurnal Teknik Sipil, 2021)
Abstract The control basin in the open channel functions as a channeled sediment control building. In this research, this research was carried out in a menhole with a beralud sill design, so that it is expected to increase the flow performance of the open channel on the downstream side. This study uses the parameter FR <1 (sub critical flow), especially the downstream side. The discharge variable varies from small to large for model 1 (talud 1: 1) and model 2 (talud 1: 2). The results of the FR research still fulfill, for model 1 on the upstream side the value of FR = 0.277 - 0.295, on the downstream side the value of FR = 0.526 - 832, while for model 2 on the upstream side the value of FR = 0.229 - 0.274, on the downstream side the value of FR = 0.185 - 0.864 ,. The depth of water in Model 1 on the upstream side H = (6.8 - 8.9) cm, on the downstream side H = (3.1 - 5.3) cm while model 2 on the upstream side H = (6.8 - 8.9) cm, on the downstream side H = (3.0 - 8.9) cm . According to the law of continuity, the amount of constant discharge, the results of the study of the amount of discharge at each point of review are different in the two models, causing a reduction in discharge, with an average value of discharge reduction (Cq), for model 1 Cq = 1.036 and for model 2 the value of Cq = 0.959 . Keywords: discharge, flow, channel